2017
DOI: 10.17219/pzp/66328
|View full text |Cite
|
Sign up to set email alerts
|

The outlook, behavior and eating habits occurring in the course of orthorexia nervosa

Abstract: Wprowadzenie. Nazwa orthorexia nervosa pochodzi z języka greckiego od słów ortho-prawidłowy, właściwy oraz orexis-apetyt, pragnienie. Pojęcie to zostało wprowadzone w 1997 r. przez amerykańskiego lekarza Stevena Bratmana, który zdefiniował ortoreksję jako patologiczną obsesję na punkcie spożywania zdrowej żywności. Cel pracy. Ocena postaw względem żywności i zdrowia, a także zachowań żywieniowych w zakresie różnorodności spożywanych artykułów spożywczych oraz stosowania ograniczeń w spożywaniu jedzenia wśród o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
3
4
0
Order By: Relevance
“…Our research has pointed to the lower risk of ON tendency (regardless of the cut-off limit in ORTO-15) among the respondents in the upper tertile of ‘High-sugar products & snacks’ and ‘Fatty products & dressings’ patterns. People with ON avoid foods rich in sugar, fat and salt [13,24,41], which is confirmed by our results. In addition, in our study greater ON tendency (for both cut-offs in ORTO-15 test) in people from the upper tertile of ‘Fresh products & nuts’ pattern was observed.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our research has pointed to the lower risk of ON tendency (regardless of the cut-off limit in ORTO-15) among the respondents in the upper tertile of ‘High-sugar products & snacks’ and ‘Fatty products & dressings’ patterns. People with ON avoid foods rich in sugar, fat and salt [13,24,41], which is confirmed by our results. In addition, in our study greater ON tendency (for both cut-offs in ORTO-15 test) in people from the upper tertile of ‘Fresh products & nuts’ pattern was observed.…”
Section: Discussionsupporting
confidence: 88%
“…Orthorexic individuals represented very specific eating habits, among others they avoid foods that may include genetically modified ingredients or pesticides, foods high in salt or sugar, and foods high in fat [24,40]. Previous research has shown that individuals eating whole wheat cereals, as well as fruits and vegetables more frequently were characterized by higher ON tendency compared to others [41]. However, despite the fact that ON is characterized by very specific eating behaviors, still little is known about food intake frequency in relation to this disorder [12,41].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be assumed that due to the contrasting eating habits of people showing only ON tendency ("ON and without ED") and only ED symptoms ("ED and without ON"), no differences were found in the eating habits of people within the group "ON and ED." In addition, these people were characterized by less frequent consumption of sugar-rich and refined products, which was confirmed by the results of the previous studies on ON [10,26,27] and both AN subtypes-restrictive and binge eating or purging [58,59]. At the same time, people who showed both ON tendency and ED symptoms ("ON and AN") often consumed meat and meat products (upper tertile of DP).…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies that analyzed the occurrence and symptoms of ON have focused on the eating behaviors to some extent. The researchers first assessed ON tendency in groups following special diets, especially a vegetarian or vegan diet [22][23][24][25], and evaluated the frequency of food intake [26]. To date, other eating habits or dietary patterns (DPs) of people showing ON tendency have only been rarely studied [10,27].…”
Section: Introductionmentioning
confidence: 99%